[Aerial View of School at Kirkjubæjarklaustur] - Streng, Evelyn Fiedler (1975)
Photograph of a school turned hotel at Kirkjubæjarklaustur from above. The white, L-shaped building is visible to the right, covered in rectangular windows and a dark, flat roof. Several buses and cars sit outside the building on the dark, paved road. Another white, rounded roof building is visible to the left in a circular patch of dark ground. A white, winding river broken up by dark deposits throughout covers the background, weaving through the green plains. Brown rock formations sit along the yellow grass-covered mountain side in the foreground, a woman in a yellow shirt sat on it.